Evaluation of Candida Species on Food and Non-Food Contact Surfaces among Students Residing in School Hostels in a Tertiary Institution, Ile Ife, Osun State, Nigeria - A. A Adewoyin; Olarinde Olaniran; S. O Awoniyi; A. B Bidmus; O. C Boriwaye (Journal of Experimental and Molecular Biology)
Candida species are significant opportunistic fungal pathogens that can cause various diseases, particularly among individuals with compromised immunity. While there is plenty of literature on Candida in clinical and public settings, incidence on surfaces within student residence halls is still not well understood. The distribution and frequency of Candida species were assessed on surfaces that come into contact with food and non-food items at the Obafemi Awolowo University residence halls in Ile-Ife, Nigeria. Seven out of nine residence halls of the university were studied using a cross-sectional investigation. Sterile swabs were used to collect surface samples from 50 rooms, which were subsequently processed on Hi Chrome Candida Differential Agar and Sabouraud Dextrose Agar. Data analysis was done using the Chi-square test with a significance level of p < 0.05. It was found that Candida species were fairly common, with an occurrence rate of 86%. The contamination rate on non-food contact surfaces was 64% compared to 76% on food contact surfaces. Its dominating species was Candida glabrata, which comprised 28%, followed by Candida albicans 6%, and Candida tropicalis was also 6%. More pronounced co-infections were noticed at the postgraduate hall: food-contact surfaces between the Candida albicans and Candida glabrata comprised 28.6%. The Moremi Hall recorded the greatest percentage of total contamination at 26%. The results stress the need for improved hygienic practices, routine check-ups, and public health programs to avoid opportunistic infections among students, as well as the need to turn attention to the possible danger of fungal contamination in communal living facilities.